2020
DOI: 10.4314/ijbcs.v14i7.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation des méthodes de piégeage des termites au nord du Burkina Faso

Abstract: En Afrique de l’Ouest, les termites sont communément utilisés comme alimentation protéinique pour la volaille. Cette étude avait pour objectif de tester et d’améliorer une méthode traditionnelle de collecte des termites par piégeage avec un récipient renversé, au Nord du Burkina Faso. Des essais ont été menés avec deux genres de termites (Macrotermes et Odontotermes) afin d’évaluer l’effet des saisons, des substrats, des récipients et de l’exposition au soleil sur leur piégeage. Six substrats ont été utilisés … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Their effectiveness for trapping termites had already been mentioned by Farina et al and Ouedraogo [23,24]. Recently, Dao et al [14] also observed that terra cotta pots were more effective to collect Macrotermes spp. and Odontotermes spp.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Their effectiveness for trapping termites had already been mentioned by Farina et al and Ouedraogo [23,24]. Recently, Dao et al [14] also observed that terra cotta pots were more effective to collect Macrotermes spp. and Odontotermes spp.…”
Section: Discussionmentioning
confidence: 82%
“…Substrates, however, have to be selected according to the termite species targeted. Recent experiments made in Northern Burkina Faso [14] showed that Macrotermes spp. are preferably attracted by sorghum stems and much less by cow dung and mixtures containing cow dung, as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Les insectes constituent des sources alimentaires durables pour l'homme et ses animaux d'élevage (Kenis et al, 2014;Dao et al, 2020 ;Ganda et al, 2020). Leur utilisation pourrait donc contribuer à réduire l'insécurité alimentaire.…”
Section: Introductionunclassified